Keanekaragaman Semut di Wilayah Evergreen dan Savana Bekol Taman Nasional Baluran Situbondo, Banyuwangi, Jawa Timur - Putri, Nurhaliza Alya; Fahidaturrochmah, Ulfatu; Setiawan, Rocie Hendi; Yusniati, Euis; Afifah, Alieffia Nur; Noor, Meiry Fadilah; Ridhwan, Muhammad (BIO-EDU: Jurnal Pendidikan Biologi, 2024)
Baluran National Park is a conservation area with various types of ecosystems including seasonal forests, beaches, savannas, evergreen forests, and mangroves. Baluran National Park has very high biodiversity potential. Ants are insects with a high level of diversity that can live in various habitats. This study was conducted to add information about the diversity of ants that inhabit Baluran National Park which has not been widely studied. The research method used was pit trap (PSM) and umpang trap in evergreen forest and bekol savanna, Baluran National Park. The results obtained were 15 genera from 5 subfamilies including Ponaerinae, Myrmicinae, Formicinae, Cerapachyinae, and Pseudomyrmicinae. Subfamily Myrmicinae has the highest number of individuals among other subfamilies.